PRODUCTIVE INNOVATIVE TECHNOLOGIES IN SCHOOL RUSSIAN LANGUAGE TEACHING - Elmuratova, Sayora Abdullaevna; Kenesbaeva, Umida Zhalgasbaevna (SCIENCE and SOCIETY, 2026)
The article addresses the issue of implementing productive innovative technologies in the practice of teaching the Russian language at school. The study aims to identify pedagogical conditions and methodological mechanisms that determine the effectiveness of digital, project-based, and communicatively oriented technologies in Russian language lessons in general education schools. The methodological framework is based on the principles of the system-activity and competence-based approaches. A conclusion is drawn about the need for systematic methodological support of the teacher’s innovative activity.